Strategic Business Decision-Making On Talent Management Scenarios To Support The Vision Of Growing Into A Large-Scale Company (Case Study Of G Communications Agency) - Prabowo, R. Radityo Putro (Jurnal Ilmiah Poli Bisnis, 2023)
In the communications consultation or agency, people or talents are the bread and butter of the company since they play crucial roles in setting up the collaboration scheme, quality of service, and the company’s culture. Therefore, talent management becomes significantly crucial for the company to strive. G Communications agency is a local agency in Jakarta that has a vision to be a large-scale company but is facing difficulties particularly in its talent management since most of its talents are in contract-based employment. This study aims to help the company determine the best hiring scheme from the three alternatives derived from cost and benefit analysis and later being calculated using SMART method. The result shows that alternative 1 with highest cost and value, and alternative 3 with lowest cost and value were performing below the trend line. Meanwhile, alternative 2 as the intermediate choice was performing above the trend line. The sensitive analysis also shows that despite changes in the weight for each group, the ranking of each alternative remains unchanged. Therefore, can be concluded that the alternatives are not sensitive nor easily perturbed by the change of the aggregate of the weighted value.